REPELLENCY OF CELERY ESSENTIAL OILS (Apium graveolens L.) AGAINST Spodoptera frugiperda (Lepidoptera: Noctuidae) IN THE LABORATORY - Alif, Trisnani; Wahidah, Fita Fitriatul (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2021)
Repellency of celery essential oil (Apium graveolens L.) against Spodoptera frugiperda (Lepidoptera: Noctuidae) in the laboratory. Essential oil is one of the ingredients that has repellent ability to herbivorous insects. Celery is one of plants containing essential oil which may also have the repellent ability. This study was aimed to determine the differences in the repellent ability of celery essential oils compounds that were taken from 3 different locations against S. frugiperda in the laboratory. This research was arranged in a factorial completely randomized design (CRD) with two factors. The first factor was the origin of the celery plants (Malang, Surabaya, and Lamongan) and the second factor was the concentration level of essential oils (1000, 2000, and 3000 ppm) which was repeated three times. The reliability test was carried out using filter paper method. The results showed that the essential oil extracted from celery originated from Malang with 3000 ppm concentration had the highest percentage level of repellency (level 5) that reached 93.33% of repellency. Location and concentration factors had no different effect on S. frugiperda larvae repellency. There was no correlation between location and concentration on the repellency of S. frugiperda larvae.